"Dr House" - gra i semiologia - Zbigniew Kloch (Images)
The paper describes how the characters of House, M.D. interact and relate to each other; it also discusses the role played by specific, semantically charged means of constructing narration. On one hand, the show largely maintains the model of a conventional medical drama, on the other, it deconstructs many of the characteristics inherent in the genre. The paper also attempts to explain the show’s huge popularity (for a certain time in the United States alone it reached 27 million viewers) achieved in spite of going beyond what an average viewer would expect, primarily by the show’s construction and by evoking ideas outside a classic medical drama.